Analisis Aspek Manajemen Waktu pada Event Festival Bingen 2022 (Studi pada Divisi Logistik CV. Soundtrack Indonesia, Palembang) - Destia Ramdini; Djohan, Muhammad Iqbal; Wibowo, Budi (Journal of Event, Travel and Tour Management, 2023)
In organizing an event there will be various divisions involved including the logistics division, one of the success factors of an event is the supply of goods from the logistics division, the logistics division will provide goods and distribute them to other divisions, the application of time management is one aspect that needs to be Paying attention to managing time properly will produce maximum results, so that the supply of goods by the logistics division will be more effective. This research discusses how the implementation of time management by the logistics division at the event Bingen Festival 2022. The research method used is qualitative research. Sources of research data conducted are from interviews and documentation. From the results of the study it was concluded that the logistics division has implemented several aspects of time management but there are still indicators that become notes for the logistics division that can be applied in the future.